Remimazolam in pediatric ambulatory anesthesia: a critical review and clinical perspective - Zhang, Yi; Liu, Hongchen; Wang, Linyun; Guo, Shuang; Zeng, Qingjun; Cui, Haishan; Li, Kaiyun (Frontiers in Medicine, 2025)
The management of anesthesia for pediatric day surgery demands rapid onset, precise control, and predictable recovery. Remimazolam, an ultrashort-acting benzodiazepine with esterase-dependent metabolism, theoretically meets these needs. However, current pediatric evidence relies primarily on small observational studies with methodological limitations; data for infants under 2 years and long-term neurodevelopmental outcomes remain virtually absent. We conclude that while remimazolam holds promise, its use must be cautious and restricted to carefully selected scenarios until robust randomized controlled trials become available.